2018
DOI: 10.1108/lodj-01-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Implicit change leadership, change management, and affective commitment to change

Abstract: Purpose The purpose of this paper is to examine differences in implicit change leadership schemas and their relationship with change management (CM) of employees of academic institutions and business enterprises. Design/methodology/approach This study used a quantitative approach through surveys with 645 employees in academic institutions and business enterprises. Path analysis and regression were conducted to determine the relationships between the constructs. Findings Results show that CM mediates the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…Second, this study focused on the experiences of workers in the Philippines. Studies have suggested that national culture and organizational context may influence employee preferences on leadership traits (Subramaniam et al , 2010; Hechanova et al , 2018). Future studies on crisis leadership may be conducted in other contexts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, this study focused on the experiences of workers in the Philippines. Studies have suggested that national culture and organizational context may influence employee preferences on leadership traits (Subramaniam et al , 2010; Hechanova et al , 2018). Future studies on crisis leadership may be conducted in other contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we take inspiration from implicit leadership theory (ILT), which is “a follower-centric perspective that assumes that followers have their own schemas of an ideal leader” (Hechanova et al , 2018, p. 917). Particularly, ILT examines patterns of preferred leadership characteristics that followers carry in their minds (Eden and Leviatan, 1975).…”
Section: A Follower-centered Approach To Crisis Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases had to belong to specific industries (for example, manufacturing, services, and commerce and tourism) and range in size, as we sought to include very different kinds of change implementation, in line with previous research (e.g. Paglis & Green, 2002;Hechanova, Caringal-Go, & Magsaysay, 2018). As a result, 1,280 middle managers (with a change implementation experience in the previous three years) were contacted, of whom 459 provided complete and valid data, producing a response rate of approximately 36 per cent.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…October 2021 edition Vol.17, No.35 www.eujournal.org 132 leaders must be skillful in engaging with the people to achieve organizational goals (Hechanova et al, 2018).…”
mentioning
confidence: 99%